1983
DOI: 10.1002/jsfa.2740341008
|View full text |Cite
|
Sign up to set email alerts
|

Yield variation of wheat and barley in Britain in relation to crop growth and soil conditions—A review

Abstract: Yields of cereals in Britain vary between sites and between years, and average farm yields are less than half of the calculated potential maximum yield. Yield variation is discussed in relation to soil conditions and root growth. An analysis of yield and its components of winter wheat for several sites over several years shows that yield is strongly correlated with number of grains per ear, and number of ears per unit area. These components of yield are influenced by environmental conditions during the reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 95 publications
3
19
0
Order By: Relevance
“…Of the yield components, grain number/unit area was related most strongly with grain yield (r = 0.89, P < 0.001). Other studies (Gallagher et al 1975;Gales 1983;Fischer 1985;Anderson 1986;Thorne & Wood 1987;Acevedo et al 1991) have also shown high correlations between grain yield and grain number/unit area. Significant relationships did occur with ears/unit area (r = 0.62, P < 0.001) and grains/ ear (r = 0.35, P < 0.05).…”
Section: Yield and Yield Componentsmentioning
confidence: 82%
“…Of the yield components, grain number/unit area was related most strongly with grain yield (r = 0.89, P < 0.001). Other studies (Gallagher et al 1975;Gales 1983;Fischer 1985;Anderson 1986;Thorne & Wood 1987;Acevedo et al 1991) have also shown high correlations between grain yield and grain number/unit area. Significant relationships did occur with ears/unit area (r = 0.62, P < 0.001) and grains/ ear (r = 0.35, P < 0.05).…”
Section: Yield and Yield Componentsmentioning
confidence: 82%
“…Morishima, Oka and Chang (1967) and Hsu and Walton (1971) classified wheat varieties as 'ear number' or 'ear length' types to emphasize the relative importance of ear number as a component of yield. Other researchers (Darwinkel, 1978;Nerson, 1980;Gales, 1983; Bulman & Hunt, 1988) have reported genotypic differences in ability of wheat cultivars to produce fertile tillers. A positive correlation between spike number and grain yield has been reported by Nass (1973).…”
Section: Fertile Ear Numbersmentioning
confidence: 96%
“…Air permeability on the soil cores was determined using the procedure of Green and Fordham (1975 Evidently, some degree of mutual compensation occurred between yield components (i.e., heads per plant to maintain crop yield (Gales 1983). …”
mentioning
confidence: 99%